Linkage of jockey falls and injuries with racehorse injuries and fatalities in Thoroughbred flat racing in Victoria, Australia - Morrice-West, Ashleigh V.; Thomas, Megan; Wong, Adelene S. M.; Flash, Meredith; Whitton, R. Chris; Hitchens, Peta L. (Frontiers in Veterinary Science, 2025)
IntroductionRacehorse and jockey incidents on race-days frequently occur together, yet risk factors for their occurrence have historically been investigated separately. Consideration of both horses and humans in tandem is required for a One Health approach to risk reduction. Our objectives were to therefore identify modifiable risk factors for adverse outcomes that are common or conflicting to both horses and their jockeys in Thoroughbred racing.MethodsAustralian Single National System records for the 2004/05 to 2018/19 flat racing season were merged with the corresponding Australian Racing Incident Database records. Incidence rate ratios (IRR) with 95% confidence intervals (CI) were estimated for the outcomes of racehorse musculoskeletal injury (MSI), racehorse fatality, jockey falls and jockey injury using Poisson regression. Horse-level, race-level, jockey-level and trainer-level factors associated with each adverse outcome during or post-race were identified using multivariable logistic regression.ResultsThe incidence of MSI was 21.21 (20.84, 21.59), racehorse fatalities 0.55 (0.50, 0.61), jockey falls was 3.01 (2.80, 3.24), and jockey injuries 1.79 (1.63, 1.97) per 1000 flat race starts. There was a decrease in racehorse MSI and jockey falls over the study period but no change in racehorse fatality or jockey injury incidence. In multivariable analysis, longer race distances and higher caliber races were associated with horse (p < 0.01), but not jockey, incidents. Firmer turf surfaces were associated with greater risk of both horse incidents and jockey falls (p < 0.05). Racehorses that were of older age at their first start, and/or had prior race-day injuries had a greater risk of injury and fatality (p < 0.001, p < 0.01, respectively). The most prominent risk factor for jockey fall or injury was a racehorse incident, although overall contributing to a relatively small proportion; 8.6% (n = 42/489) of jockey falls and 15.3% (n = 24/147) of injuries. Jockeys with fewer career starts were at greater risk of falling, and those with a higher percentage of last place finishing positions were at greater risk of injury (p < 0.001).DiscussionAs there were no conflicting risk factors identified between racehorse and jockey injury, policies aimed at reducing horse injury risk are also expected to benefit their riders.